General Mathematics Revision and Practice - "Rayner, D" (Oxford University Press: London, 1988)
Suitable for self-study or teacher-led courses to take GCSE and Standard Grade candidates up to A* Grade, or Scottish Credit level. This edition includes a chapter on investigations, practical problems and puzzles, to give the student problem-solving skills. It also includes Mathematics drawn out from a range of realistic everyday situations.
Keywords: Mathematics-Textbook